Drug resistance mutations in HIV pol sequences from Argentinean patients under antiretroviral treatment: subtype, gender and age issues - Jones, Leandro Roberto (2011)
We studied drug resistance mutations (DRMs) in 2623 pol sequences. Out of 94,828 amino acid substitutions that were detected, 8749 corresponded to nucleoside reverse transcriptase inhibitor (NRTI), 3765 to nonnucleoside reverse transcriptase inhibitor (NNRTI), and 7141 to protease inhibitor (PI) resistance-associated mutations. The most common DRMs were L10I, I54V, L90M, V82A, A71V, L10V, M46I, M184V, M41L, T215Y, D67N, L210W, K70R, N348I, V118I, K103N, Y181C, G190A, K101E, V108I, L100I, V90I, K101Q, and A98G. As expected, DRMs frequencies depended on viral genotype. The amounts of NRTI and PI resistance mutations among B and BF sequences from children were higher than among sequences from adults. The frequencies of PI and NRTI resistance mutations among B and BF sequences from adult men were higher than among sequences from women. Some of these observations can be explained in light of the available epidemiological information, but some cannot, indicating that further studies are needed to understand the antiretroviral resistance epidemics in Argentina.